2005
DOI: 10.2170/jjphysiol.r2133
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Mechanical Stimulation Regulates Ovarian Blood Flow via Activation of Spinal and Supraspinal Reflex Pathways in Anesthetized Rats

Abstract: Abstract:The reflex effects of noxious mechanical stimulation of a hindpaw or abdominal skin on ovarian blood flow, and the reflex pathways involved in those responses were examined in anesthetized rats. Blood flow in the left ovary was measured using a laser Doppler flowmeter, and the activity of the left ovarian sympathetic nerve and mean arterial pressure (MAP) of the common carotid artery were recorded. Stimulation of the left or right hindpaw for 30 s produced marked increases in ovarian sympathetic nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 21 publications
2
21
1
Order By: Relevance
“…Furthermore, asymmetry in the somato-sympathetic reflex has been demonstrated in studies where noxious mechanical stimulation was applied to the region of the abdomen whose spinal segment of the afferents is close to the segment of the ovarian sympathetic nerve output. Stimulation of the left abdomen induced a much stronger effect on left ovarian sympathetic nerve activity than stimulation of the right abdomen (Uchida et al, 2005).…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, asymmetry in the somato-sympathetic reflex has been demonstrated in studies where noxious mechanical stimulation was applied to the region of the abdomen whose spinal segment of the afferents is close to the segment of the ovarian sympathetic nerve output. Stimulation of the left abdomen induced a much stronger effect on left ovarian sympathetic nerve activity than stimulation of the right abdomen (Uchida et al, 2005).…”
Section: Discussionmentioning
confidence: 83%
“…Blood flow in the left ovary was measured in 12 rats using a laser Doppler flowmeter (ALF21D, Advance, Tokyo) as described previously by Uchida et al [13]. In brief, the left ovary was exposed ventrally by opening the abdominal wall.…”
Section: Animalsmentioning
confidence: 99%
“…In our laboratory, we have recently demonstrated that noxious, but not non-noxious, mechanical stimulation of the hindpaw skin in anesthetized rats exerts influence upon the ovarian blood flow and that this is attributable to reflex responses in ovarian sympathetic nerve activity and blood pressure [12,13]. It is possible that thermal stimulation also exerts reflexive effects upon ovarian blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…The OPN innervates the ovary, bursa, oviduct [3], and cranial uterine horns [1]; the axons enter through the hilum [48] and innervate the medullary and cortical region of the ovary. The OPN is mostly composed by sympathetic and sensory fibers, with a small portion of parasympathetic fibers [4, 9, 10].…”
Section: Introductionmentioning
confidence: 99%